Identification of Bacterial Isolates from Mozzarella Cheese Whey Using 16S rDNA and Assessment of Their Consortium Proteolytic Activity: Identification and Protease Activity of Cheese Whey Bacteria - Maulidiyah, Nuris; Ardyati, Tri; Dwi Jatmiko, Yoga (Journal of Tropical Life Science, 2025)
Cheese whey is the main waste from cheese production, which contains high levels of protein, lactose, and minerals. However, if not properly managed, its acidic pH and high organic load can negatively impact the environment when discharged directly. Its protein content makes it a habitat for proteolytic bacteria that are capable of producing protease enzymes to hydrolyze proteins into peptides and amino acids. Moreover, the utilization of proteolytic bacteria from cheese whey offers a biotechnological solution for waste management while opening up opportunities for industrial applications, such as fermentation and the production of functional enzymes. The aim of this study is to analyze the protease activity of single bacterial isolates and bacterial consortia isolated from cheese whey and identify isolates based on 16S rDNA. The first stage of the research was screening pathogenicity based on hemolysis analysis using a blood agar medium. The second stage tested for synergism among isolates. The ability of isolates to produce proteolytic enzymes qualitatively and quantitatively, and then the identification of proteolytic bacterial species based on 16S rDNA. Hemolysis assay of eight isolates resulted in three isolates (A8, C7, and C8) showing gamma hemolysis. The protease activity assay of three isolates was measured at an incubation period of 0-72 hours; the consortium (cn) isolate exhibited the highest activity of 0.47 U/mL U/mL. Based on the 16S rDNA sequence, isolate A8 was identified as Staphylococcus saprophyticus 36QC2CO with a similarity of 98.04%, isolate C7 was identified as S. saprophyticus WWi54 with a similarity of 97.81%, and isolate C8 was identified as Staphylococcus epidermidis 2322 with a similarity of 97.6%.